Perlindungan Hukum terhadap Anak Korban Kekerasan Seksual di Kota Surabaya - Muwahid, Muwahid (Al-Jinayah : Jurnal Hukum Pidana Islam, 2019)
Children are the future generation who require protection from violence, whether physical, psychological and sexual violence. This study seeks to uncover such problems; (1) the form of legal protection of children against sexual violence victims in Surabaya; (2) the constraints in the implementation of legal protection of children against sexual violence victims in Surabaya; (3) attempts to maximize the implementation of the legal protection of children against sexual violence victims in Surabaya. The present study is a field research. The primary data obtained through interviews while secondary data obtained from documents, law books and law journals. Data analysis technique using content analysis that is the analysis technique by describing the substance of the existing problems. The results of the research revealed that; Firstly, the form of legal protection of children against sexual violence victims in Surabaya can be seen from the two forms, they are preventive protection and repressive legal protection. Preventive legal protection is done before the sexual crimes, while the protection of repressive laws is done after the acts of sexual violence; secondly, constraints faced in the implementation of legal protection, they are; the victim is introvert, the act of hoodlum, the societies’ individual attitude that is really powerful and a lack of public understanding about children’s rights; Third, ways and means need to be done to maximize the implementation of legal protection is a way to provide understanding to parents and children about the dangers of sexual violence, and the need for strengthening the commitment and systematic and massive cooperation of law enforcement officials. Abstrak: Anak merupakan generasi penerus bangsa yang memerlukan perlindungan dari tindak kekerasan, baik fisik, psikis, dan kekerasan seksual. Dalam konteks inilah tulisan ini hadir, yaitu untuk mengetahui: (1) bentuk perlindungan hukum terhadap anak korban kekerasan seksual di Surabaya; (2) kendala-kendala dalam pelaksanaannya serta upaya untuk memaksimalkan pelaksanaan tersebut. Tulisan ini merupakan hasil penelitian lapangan, di mana data diperoleh melalui dan studi dokumen, yang selanjutnya dianalisa dengan menggunakan content analysis. Hasil penelitian ini menunjukkan; pertama, bentuk perlindungan hukum terhadap anak korban kekerasan seksual di Surabaya bisa dilihat dari dua bentuk, yakni perlindungan preventif yang dilakukan sebelum terjadi kejahatan seksual, dan perlindungan hukum represif yang dilakukan setelah terjadi tindak kekerasan seksual. Kedua, kendala-kendala yang dihadapi antara lain; tertutupnya korban, adanya aksi premanisme, sikap individualitas masyarakat yang cukup kuat dan kurangnya pemahaman masyarakat tentang hak-hak anak; ketiga, upaya yang perlu dilakukan guna memaksimalkan pelaksanaannya adalah cara memberikan pemahaman kepada orang tua dan anak mengenai bahaya kekerasan seksual, dan perlunya penguatan komitmen dan kerjasama yang sistematis dan masif dari aparat penegak hukum.